The Effect of Market Value, Profitability, and Solvency to Return of Shares in Automotive Companies Listed on the Indonesian Stock Exchange - Farraniza Artha Ridha; Nurjanti Takarini (International Journal of Economics (IJEC), 2024)
This study aims to determine the effect of market value, profitability and solvency of stock returns of automotive companies listed on the IDX. The method used in this study is a type of quantitative method with purposive sampling technique. The research sample is 70 companies. The analytical tool used in this study is the SPSS model. The secondary source used in this study was obtained from an automotive company listed on the Indonesia Stock Exchange, namely www.idx.co.id. The results of this study indicate that market value has a positive and insignificant effect on stock returns in automotive sector companies in 2018-2022. Market value (Earning Per Share/EPS) is often considered as one of the important factors influencing stock returns. EPS reflects the profit generated by the company for each outstanding share. However, there are situations where the EPS market value does not have a significant effect on stock returns. Profitability has a positive and significant effect on stock returns of automotive sector companies in 2018-2022. This is because a high profitability ratio can attract investors, increase trust, and cause an increase in demand for company shares. Solvability has a positive and significant effect on stock returns of automotive sector companies in 2018-2022. This is because debt as business capital will help maximize the company's operations so that the profits obtained will also be maximized.